5(w-3)=w-11

Simple and best practice solution for 5(w-3)=w-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(w-3)=w-11 equation:


Simplifying
5(w + -3) = w + -11

Reorder the terms:
5(-3 + w) = w + -11
(-3 * 5 + w * 5) = w + -11
(-15 + 5w) = w + -11

Reorder the terms:
-15 + 5w = -11 + w

Solving
-15 + 5w = -11 + w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-1w' to each side of the equation.
-15 + 5w + -1w = -11 + w + -1w

Combine like terms: 5w + -1w = 4w
-15 + 4w = -11 + w + -1w

Combine like terms: w + -1w = 0
-15 + 4w = -11 + 0
-15 + 4w = -11

Add '15' to each side of the equation.
-15 + 15 + 4w = -11 + 15

Combine like terms: -15 + 15 = 0
0 + 4w = -11 + 15
4w = -11 + 15

Combine like terms: -11 + 15 = 4
4w = 4

Divide each side by '4'.
w = 1

Simplifying
w = 1

See similar equations:

| P=3n | | 5p=6p+12 | | 62-3x=8x+15 | | 19a-7-17a+23=-14 | | 14=7x+4-5x | | 5x+9=58x-2 | | 5-0.03x=0.2-0.05x | | 2n-11+2n-11+n=18 | | 2-3m=m | | y=4x-31 | | 7x+10=8x+5 | | -6y+x=8 | | 15y-8-15y=17 | | -6x-5y=8 | | -3b=11 | | x-3/(x/4)-(4/x) | | x-3/((x/4)-(4/x)) | | (x^2/20+x/4+1/5)=0 | | f=11/(5)2 | | 8x=24x^2 | | 4y^2-27y+147=0 | | 4(x-7)=24 | | 5p+7q=71 | | 8+(8)/(x-5) | | 3f-4=20 | | 5/1*3/4 | | 1/5x=7/15 | | 5e+3=23 | | 5x+8888+x*(x-65)=1 | | 25x^2=49x | | x+19=19+6 | | 5x-88+x*(x-65)=8888 |

Equations solver categories